2018
DOI: 10.3847/1538-4357/aad090
|View full text |Cite
|
Sign up to set email alerts
|

Inside a Beehive: The Multiple Merging Processes in the Galaxy Cluster Abell 2142*

Abstract: To investigate the dynamics of the galaxy cluster A2142, we compile an extended catalog of 2239 spectroscopic redshifts of sources, including newly measured 237 redshifts, within 30 arcmin from the cluster center. With the σ-plateau algorithm from the caustic method, we identify 868 members and a number of substructures in the galaxy distribution both in the outskirts, out to ∼3.5 Mpc from the cluster center, and in the central region. In the outskirts, one substructure overlaps a falling clump of gas previous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 87 publications
1
27
0
1
Order By: Relevance
“…The infall zone extends approximately up to 2 h −1 Mpc from the cluster centre. This agrees with the clustercentric distance limit for the cluster members in the caustic diagram by Liu et al (2018). In this region, the stellar ages and star-formation rates of galaxies change rapidly (Einasto et al 2018b).…”
Section: Filaments and Groups In The Supercluster And In The Cocoonsupporting
confidence: 85%
“…The infall zone extends approximately up to 2 h −1 Mpc from the cluster centre. This agrees with the clustercentric distance limit for the cluster members in the caustic diagram by Liu et al (2018). In this region, the stellar ages and star-formation rates of galaxies change rapidly (Einasto et al 2018b).…”
Section: Filaments and Groups In The Supercluster And In The Cocoonsupporting
confidence: 85%
“…For both clusters, the observed hg þ ð#Þi profiles are better fitted by the NFW model having an outward-steepening density profile. Abell 2142 is a nearby cluster at z l ¼ 0:091 perturbed by merging substructures (e.g., Okabe and Umetsu 2008;Umetsu et al 2009;Liu et al 2018). The radial curvature observed in the hg þ i profile of Abell 2142 is highly pronounced, so that the power-law SIS model is strongly disfavored by the Subaru weak-lensing data.…”
Section: Nfw Modelmentioning
confidence: 99%
“…The radial curvature observed in the hg þ i profile of Abell 2142 is highly pronounced, so that the power-law SIS model is strongly disfavored by the Subaru weak-lensing data. From the best-fit NFW model, the mass and concentration parameters of Abell 2142 are constrained as M 200c ¼ ð9:1 AE 1:9Þ Â 10 14 h À1 M and c 200c ¼ 4:1 AE 0:8 (Umetsu et al 2009;Liu et al 2018).…”
Section: Nfw Modelmentioning
confidence: 99%
“…For example, in the case of Abell 1835, the upper limit of redshift offset corresponds to ∆v < 600 km s −1 (Ueda et al 2017). Liu et al (2018) measured the redshift offset of the cold fronts relative to the cluster average in Abell 2142 to be 810 ± 330 km s −1 . For the Perseus cluster, Hitomi Collaboration et al (2018) reported the velocity gradient with a 100 km s −1 amplitude across the cluster core, which is likely associated with a sloshing motion in the plane of the sky.…”
Section: Los Gas Sloshingmentioning
confidence: 99%